Medical immunity, international law and just war theory. Issue 4 (16th October 2018) - Allhoff, Fritz; Potts, K
Abstract : Under customary international law, the First Geneva Convention and Additional Protocol I, medical personnel are protected against intentional attack. In § 1 of this paper, we survey these legal norms and situate them within the broader international humanitarian law framework. In § 2, we explore the historical and philosophical basis of medical immunity, both of which have been underexplored in the academic literature. In § 3, we analyse these norms as applied to an attack in Afghanistan (2015) by the United States; the United States was attempting to target a Taliban command-and-control centre but inadvertently destroyed a Médecins Sans Frontières hospital instead, killing 42 people. In § 4, we consider forfeiture of medical immunity and, more sceptically, whether supreme emergency could justify infringement of non-forfeited protected status.